PENANGANAN KORUPSI BERDASARKAN HUKUM ADMINISTRASI NEGARA - Salwaa Pramiltari Annisa; Lukman Yudho Prakoso (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Eliminating deficiencies and fraud is the goal of Indonesia's national development strategy. Authorities, civil servants, social organizations, and others are trying hard to overcome both